2013
DOI: 10.18869/acadpub.3dj.1.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug Prescription Pattern among General Dental Practitioners in Rasht, Iran

Abstract: Introduction: Irrational drug prescription is a controversial issue around the world that interferes not only with the patient's life but also with the society and economy. Despite few studies, there is no enough data on the prescription habits of dental practitioners. So, we aimed at evaluating the same issue in Rasht, Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
1
12
1
2
Order By: Relevance
“…In this respect, the most frequently prescribed pharmaceutical items in one script was equal to 2.59 ± 1.13. This value was higher than the average number of prescribed items in others studies that found 2.03 [1] and 2.3 [25] but it was lower than the 2.64 obtained in Rasht, Iran [29]. Moreover, in most studies, the average number of drugs prescribed in the prescriptions written by dentists was estimated by 2 to 3 items and observations also showed that dental practitioners often prescribed one or two analgesic and antiinflammatory items along with one or two antibiotic items to their patients although this prescription pattern demonstrated great diversity in their prescriptions.…”
Section: Discussioncontrasting
confidence: 74%
“…In this respect, the most frequently prescribed pharmaceutical items in one script was equal to 2.59 ± 1.13. This value was higher than the average number of prescribed items in others studies that found 2.03 [1] and 2.3 [25] but it was lower than the 2.64 obtained in Rasht, Iran [29]. Moreover, in most studies, the average number of drugs prescribed in the prescriptions written by dentists was estimated by 2 to 3 items and observations also showed that dental practitioners often prescribed one or two analgesic and antiinflammatory items along with one or two antibiotic items to their patients although this prescription pattern demonstrated great diversity in their prescriptions.…”
Section: Discussioncontrasting
confidence: 74%
“…since it is the first choice in dentistry so prescribed by maximum number of students (79) in dentistry. [ 7 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Rational drug prescription is defined as using the least number of drugs to obtain the best possible effect in the shortest period and at a reasonable cost. [ 6 7 ] Medical students and interns should be periodically assessed on prescribing knowledge and skills during their training as a means of minimizing prescribing errors. [ 8 9 10 ] A firm grounding in the principles of prescribing and therapeutics, an understanding of how drugs work, and a basic knowledge about commonly used drugs are essential for all medical graduates.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the average error in the questionnaire between 10 and 20 (4.3 ± 13.7) was found. Kia et al examined 850 prescriptions written by dentists found that 97.2% of prescriptions had one or more errors ( Kia et al, 2012 ). Nezafati et al found that 98.05% of prescriptions written by dentists in Tabriz, had errors ( Nezafati et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%